Artificial Intelligence as an Assistant and Generator of Student Learning in Islamic University - Abdurrahman, Abdurrahman; Hidayah, Fathi; Dhiauddin, Dhiauddin; Fanani, Zainuddin (AT-TA'LIM, 2024)
This research examines the knowledge and use of Artificial Intelligence in Education (AIEd) by students at three Islamic universities in Indonesia, namely Universitas Al-Qolam Malang (UQM), Institut Agama Islam Ibrahimy Banyuwangi, and Institut Agama Islam Al Muslim Aceh. This survey was conducted at the undergraduate and postgraduate levels. This study used a mixed-methods method with a multi-site case study design. Data were collected online through quantitative surveys and qualitative interviews, using three analytical techniques: pattern matching, explanation building, and logic models. The findings of the research indicate that the level of student knowledge about AIEd is still relatively low. The majority of students are not familiar with AIEd and its benefits in the learning process. Students use AIEd for various academic purposes. As a learning assistant, AI is used to access library materials (books, journals, and kitab kuning), text translation, infer PDF content, and plagiarism detection. As a generative AI, students use AI for citation management, paraphrasing texts, creating paper outlines, and even writing part or all of a paper. Students generally have a positive view of AIEd's prospects in the Islamic PT environment. They believe that AIEd can help improve the quality of learning and support the achievement of their learning goals. This research provides an overview of AIEd’s potential to revolutionize the design, processes, and learning assessment systems in Islamic universities. So the recommendation from these findings is the need for socialization, education and training efforts to increase student knowledge about AIEd and how to use it effectively.